The Impact Of Foreign Banks Entry On The Competitiveness Of Domestic Banks : The Case For Malaysian Banks - Nik Muhammad, Nik Ahmad Mukharriz (2005)
This research discovers that based on a study of five variables of domestic Malaysian banks during the period 1988-98, increased foreign bank competition lowers interest and non-interest margins, overhead costs, and loan loss provisions, but boost the before tax profits, of domestic Malaysian banks.